The Effect of Pain and Swelling Related to Third Molars on Oral Health-Related Quality of Life - Bharati R. Doni; Arunpriya Srinivasan; Rakhi Issrani; Ruchi Agrawal; Santosh Rayagouda Patil; Mohammad Khursheed Alam (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate the effect of pain and swelling related to third molars on patients' quality of life prior to third molar surgery. Material and Methods: The effects on quality of life with reference to oral health of 246 healthy patients seeking treatment of third molars were analyzed using the 14-item Oral Health Impact Profile (OHIP) questionnaire before surgery. The patients' sociodemographic characteristics, medical and dental history, reasons for third molar removal were recorded. Adverse effects of pain and swelling on oral health-related quality of life were recorded. Results: The mean age of the patients included in the study was 23.15 years, with maximum male patients and the mean OHIP-14 score of 8.01 ± 7.51. About 36.97% of patients reported that their chief complaint was pain/swelling due to third molar infection, and 27.9% of subjects reported one or more of the 14 OHIP items. The odds of reporting for age with ≥25 years was approximately 2 times greater than age with ≤25 years (OR=1.56, 95% CI: 1.01-2.57) and tooth loss due to traumatic history (OR=3.14, 95% CI: 2.12-6.54). Conclusion: Adverse influences on quality of life were seen in a significant number of patients seeking third molar removal. The probabilities increased by 3-fold for patients who had experienced pain or swelling than asymptomatic individuals.